2017
DOI: 10.1111/jcmm.13096
|View full text |Cite
|
Sign up to set email alerts
|

Comparing six antihypertensive medication classes for preventing new‐onset diabetes mellitus among hypertensive patients: a network meta‐analysis

Abstract: Hypertensive patients usually have a higher risk of new‐onset diabetes mellitus (NOD) which may trigger cardiovascular diseases. In this study, the effectiveness of six antihypertensive agents with respect to NOD prevention in hypertensive patients was assessed. A network meta‐analysis was conducted to compare the efficacy of specific drug classes. PubMed and Embase databases were searched for relevant articles. Results of the pairwised meta‐analysis were illustrated by odd ratios (OR) and a corresponding 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
2
6
0
1
Order By: Relevance
“…Previous studies reported that CCB combined with ARB had metabolically neutral effects [6]. Our study also showed that the use of RASI in addition to CCB did not show a significant reduction of the development of NODM.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies reported that CCB combined with ARB had metabolically neutral effects [6]. Our study also showed that the use of RASI in addition to CCB did not show a significant reduction of the development of NODM.…”
Section: Discussionsupporting
confidence: 60%
“…In patients with T2DM, the incidence of CVD is about two- and four-times higher than the general population [5]. Therefore, hypertensive patients have a relatively higher risk of new-onset DM (NODM) and this may trigger further cardiovascular diseases [6]. Antihypertensive drug impacts on the blood glucose level are diverse according to the class of those drugs [7][9].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that beta blockers and diuretics are associated with worsening glucose tolerance, CCBs are neutral, and medications which interfere with the renin-angiotensin system are associated with improved glucose tolerance 32 . In a recent network meta-analysis of medications to prevent new-onset diabetes, diuretics were associated with increased risk of new-onset diabetes versus placebo, but beta blockers were not; CCBs were neutral 33 . In in vitro models of insulin secretion, inhibition of L-type calcium channels by nifedipine decreases glucose stimulated insulin secretion from islets, which would correlate with post-prandial hyperglycemia 34 .…”
Section: Discussionmentioning
confidence: 99%
“…В сентябре 2017 г. вышел метаанализ, проанализировавший на примере 5 основных классов антигипертензивных средств риск развития новых случаев СД [46]. Было выявлено, что иАПФ и сартаны могут предотвращать развитие новых случаев диабета.…”
Section: факторы риска (аг сд ожирение…)unclassified